E-CLASSROOM LANGUAGE: A CONVERSATION ANALYSIS OF SYNCHRONOUS INSTRUCTIONS DURING THE COVID-19 OUTBREAK - Hany Apriliani; Nenden Sri Lengkanawati (Premise: Journal of English Education and Applied Linguistics, 2023)
Normally, when teaching in traditional classrooms, teachers would use different types of classroom language for a variety of purposes such as greetings, giving instructions, asking questions, and giving feedback. This study seeks to examine teachers’ use of classroom language in synchronous virtual classrooms and the extent to which it facilitates learning opportunities for EFL learners. Under the qualitative research framework, video recordings of online instructional activities were analyzed using a conversation analysis approach. The results show that the majority of expressions used in online synchronous instructions were quite similar to those used in traditional classrooms except for the expressions like “let me share my screen,” “turn on the camera,” and “I will mute everyone”. The results also show that teachers’ e-classroom language use provided learning opportunities for students by means of recast, scaffolding, and extended wait time for students’ turns.